If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4z + 6z = 10 Combine like terms: 4z + 6z = 10z 10z = 10 Solving 10z = 10 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Divide each side by '10'. z = 1 Simplifying z = 1
| 27x-2=47 | | 4(x-3)+2=26 | | 7m+n=2forn | | 16x-8=14x+8 | | -3-(2-3x)=2x-(5-x) | | (3x-c)-5=x-7 | | 13-2n=-37 | | a+b(x-y)=cforx | | 20x+10=50 | | 2(x+4)-5(2x-1)= | | 11x-3=10x+5 | | n^2+n=6 | | 12-1.2(x-5)=22-2(5-3s) | | 2x+3/3=x-1/x-2 | | 3+(9n+5)=35 | | 5x+9x+2x+20=52 | | Ax+by=cforx | | n=300 | | 21-(x-5)=-4x+12 | | 3-7x=10-(x+1) | | 3/2u+3/8=5/4+9/2u | | 7+12x=115 | | 7+12x=105 | | 12x-(-2x+9)=26 | | 8u-6=9u-9 | | -10-(5x+2)=8 | | x+71=60 | | -8m-38=5(1-4m)-7 | | 1035/42 | | -3(3s-6)-18=-3(5s+0)-5 | | 3(3v-1)=6v-2 | | 4x-4=x+(17-4x) |